How Does Mentoring Affect the Creative Performance of Mentors: The Role of Personal Learning and Career Stage - Xu, Shuang; Liu, Pingqing; Yang, Zheng; Cui, Zunkang; Yang, Fang (Frontiers in Psychology, 2021)
Mentoring has become a vital strategy for improving employee performance and organizational development. Previous literature made a detailed study on mentees’ benefits. Mentors’ creative performance improving from mentoring, however, only draws little attention. This paper extends this line of inquiry by shedding light on whether, how, and when mentoring affects the mentors’ creative performance, which is a crucial topic in research and practice. Based on the conservation of resources theory and relational cultural theory, this paper investigates the influence mechanism and boundary conditions of mentoring on mentors’ creative performance by conducting a multi-source empirical study in China. The result shows that there is a positive impact of mentoring on mentors’ creative performance. We also reveal that the relationship is mediated by personal learning, especially the relational job learning dimension. Furthermore, this paper finds that mentors’ career stage moderates the relationship between mentoring and personal learning, namely, the relationship is stronger among mentors at later career stage. The empirical findings have implications for understanding how mentors’ creative behavior benefits in mentoring and can be beneficial for developing targeted measures to promote competitive advantages for organizations.